Metabolic profile and potential mechanisms of Wendan decoction on coronary heart disease by ultra‐high‐performance quadrupole time of flight‐mass spectrometry combined with network pharmacology analysis. Issue 1 (10th November 2022) - Wang, Qi; Chen, Jiayun; Zhang, Yezi; Xu, Danping; Wu, Huanlin; Lin, Pei; He, Liangliang; Qin, Zifei; Yao, Zhihong
Abstract : Wendan decoction, a well‐known classical traditional Chinese medicine prescription, has been widely used in the clinical application of coronary heart disease for thousands of years. However, due to a lack of research on the overall metabolism of Wendan decoction, the bioavailable components responsible for the therapeutic effects remain unclear, hindering the revelation of its mechanisms against coronary heart disease. Consequently, an efficient joint research pattern combined with characterization of the metabolic profile and network pharmacology analysis was proposed. As a result, a total of 172 Wendan decoction‐related xenobiotics (57 prototypes and 115 metabolites) were detected based on the exploration of the typical metabolic pathways of representative pure compounds in vivo, describing their multi‐component metabolic characteristics comprehensively. Subsequently, an integrated network of "herbs‐bioavailable compounds‐coronary heart disease targets‐pathways‐therapeutic effects" was constructed, and its seven compounds were finally screened out as the key components acting on five main targets of coronary heart disease. Overall, this work not only provided a crucial biological foundation for interpreting the effective components and action mechanisms of Wendan decoction on coronary heart disease but also showed a reference value for revealing the bioactive components of traditional Chinese medicine prescriptions.